The Political Economy of Policy Centralization: Direct Versus Representative Democracy - Michela Redoano; Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper examines policy centralization outcomes in a two-jurisdiction, political economy model of public good provision choices with heterogeneous policy preferences and interjurisdictional policy spillovers, under alternative democratic choice procedures, namely, direct democracy and representative democracy. We show that policy centralization is more likely to occur if the choice to centralize is made by elected policymakers rather than by referendum. The reason for this result is that delegation of the harmonization choice to elected policymakers can effectively act as a policy commitment device by a pro-centralization jurisdiction and induce a reluctant partner to cooperate. In these situations, policy centralization will result in policies converging towards the choice preferred by the reluctant partner, rather than in a dilution of policy preferences.
Keywords: 330; international cooperation; trade and environmental policy negotiations